Case Study of Second Language Acquisition: What Contributes to Speaking Proficiency - Wildan I Asyhar (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2019)
The purpose of this study is to investigate: what contributes to speaking proficiency in second language acquisition. In this case the researcher intends to investigate how language input, conducive environment, and motivation influence studentsâ€™ speaking proficiency. To develop a deep understanding to the success of speaking proficiency, a qualitative research was conducted. Further, since this study intended to figure out the cause or effect relationship between behavior and outcome, a descriptive qualitative was used to describe the process of succeeding the subjectsâ€™ speaking proficiency. The learner who is not less than 12 years old is the potential subject. The subject should qualify to have categorized as â€œgoodâ€ level of speaking proficiency minimum based on the test. Research instruments used are in-depth interview and questionnaire. From the finding, the result shows that three aspects, language input, conducive learning environment, and motivation, have contribution in deciding the level of English speaking proficiency.